35 Is down syndrome-associated arthritis (Da) a distinct disease from juvenile idiopathic arthritis (Jia)?. (22nd November 2019) - Foley, Charlene; Floudas, Achilleas; Fearon, Ursula; Killeen, Orla
Abstract : Background: DA, an erosive, polyarticular-RF-negative arthritis with predominance in the small joints of the hands and wrists is 20-times more common than JIA. Little is known about DA pathogenesis. We hypothesise that it is a distinct disease from its closest ILAR subtype, polyarticular-RF-negative-JIA. Aim(s): Compare B–cell–subsets and T–cell–cytokine profiles; synovial membrane immunohistochemistry and synovial–fibroblast–cell (SFC) functionality in DA and polyarticular–RF–negative–JIA. Identify whether polyarticular–RF–negative–JIA susceptibility loci, HLA–DQB1/HLA–DQA2 and PTPN22 are present in DA. Methods: Multicolour-flow-cytometry, FlowJo and SPICE-software were used to analyse B-cell-subsets and T-cell-cytokine expression. Synovial tissue was obtained through ultrasound-guided biopsy (DA n=3; JIA n=4) and analysed by immunohistochemistry. DA-SFC and JIA-SFC migration was assessed by wound-repair scratch assays; invasion by Biocoat Matrigel™ Invasion Chambers; and bioenergetic activity using the XFe96-Flux-analyser. Real-time-PCR assessed glycolytic gene expression. Arthritis Research UK Centre for Genetics and Genomics performed genotyping and analysis of HLA-DQB1/HLA-DQA2 and PTPN22 in DNA from children with polyarticular-RF-negative-JIA (n=732), DA (n=42), T21 (n=31) and HC (n =9196). Results: Children with DA had a significantly lower number of circulating B-cells compared to JIA and HC, but a greater proportion of memory B-cells compared to T21. T-cell IFN-γ and TNF-α production was significantly greater in DA compared to JIA and HC. Greater T-cell polyfunctionality was observed in DA compared to all three comparison groups. DA synovial tissue demonstrated greater lining layer hyperplasia, vascularity and inflammatory cell infiltration in DA compared to JIA. DA-SFC showed greater migratory and invasive capacity, and increased basal metabolic activity and metabolic gene-expression compared to JIA-SFC. The MAF for polyarticular-RF-negative-JIA associated variants HLA-DQB1/HLA-DQA2 and PTPN22 were not similar in DA. Conclusion: Significant differences were observed in the immuno-histological and genetic profiles of DA and polyarticular-RF-negative-JIA that may explain the erosive phenotype observed in DA, and suggest they may be distinct diseases.